Leukocyte-Derived IFN-α/β and Epithelial IFN-λ Constitute a Compartmentalized Mucosal Defense System that Restricts Enteric Virus Infections - Mahlakõiv, Tanel; Hernandez, Pedro; Gronke, Konrad; Diefenbach, Andreas; Staeheli, Peter (PLoS pathogens, 2015)
Epithelial cells are a major port of entry for many viruses, but the molecular networks which protect barrier surfaces against viral infections are incompletely understood. Viral infections induce simultaneous production of type I (IFN-α/β) and type III (IFN-λ) interferons. All nucleated cells are believed to respond to IFN-α/β, whereas IFN-λ responses are largely confined to epithelial cells. We observed that intestinal epithelial cells, unlike hematopoietic cells of this organ, express only very low levels of functional IFN-α/β receptors. Accordingly, after oral infection of IFN-α/β receptor-deficient mice, human reovirus type 3 specifically infected cells in the lamina propria but, strikingly, did not productively replicate in gut epithelial cells. By contrast, reovirus replicated almost exclusively in gut epithelial cells of IFN-λ receptor-deficient mice, suggesting that the gut mucosa is equipped with a compartmentalized IFN system in which epithelial cells mainly respond to IFN-λ that they produce after viral infection, whereas other cells of the gut mostly rely on IFN-α/β for antiviral defense. In suckling mice with IFN-λ receptor deficiency, reovirus replicated in the gut epithelium and additionally infected epithelial cells lining the bile ducts, indicating that infants may use IFN-λ for the control of virus infections in various epithelia-rich tissues. Thus, IFN-λ should be regarded as an autonomous virus defense system of the gut mucosa and other epithelial barriers that may have evolved to avoid unnecessarily frequent triggering of the IFN-α/β system which would induce exacerbated inflammation.